Description of the immature stages of Culex (Culex) ameliae Casal and Culex (Culex) articularis Philippi (Diptera: Culicidae) - Laurito, Magdalena; Almirón, Walter Ricardo; Rossi, Gustavo Carlos (Zootaxa, 2011)
The pupa and the fourth-instar larva of Culex (Culex) ameliae Casal and Cx. (Cux.) articularis Philippi are described and illustrated for the first time. Information is provided on the distribution, bionomics and taxonomy of the species.